2011
DOI: 10.1063/1.3614475
|View full text |Cite
|
Sign up to set email alerts
|

Generic relation between the electron work function and Young's modulus of metals

Abstract: In this study, efforts were made to establish a generic relation between the Young’s modulus and the electron work function of polycrystalline metals, in which Young’s Modulus was defined as the second order derivative of interaction potential with respect to the equilibrium distance. The obtained Young’s modulus shows a sextic relation with the work function. Data of Young’s modulus and work function of polycrystalline metals, including Alkali earth metals, transition metals, and rare earth metals, can be fit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
53
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 100 publications
(62 citation statements)
references
References 14 publications
7
53
0
Order By: Relevance
“…It has been demonstrated that the mechanical behaviors (including bulk modulus, Young's modulus, hardness, and yield stress) of metals can be characterized by their electron distributions. 34,54,59,[62][63][64] As shown in, our predicted EWF of Mg agrees well with previous experimental 52 and theoretical data. 65 By selecting different reference states, the variations of EWF (Du 1 and Du 2 ) are defined as:…”
Section: Resultssupporting
confidence: 93%
“…It has been demonstrated that the mechanical behaviors (including bulk modulus, Young's modulus, hardness, and yield stress) of metals can be characterized by their electron distributions. 34,54,59,[62][63][64] As shown in, our predicted EWF of Mg agrees well with previous experimental 52 and theoretical data. 65 By selecting different reference states, the variations of EWF (Du 1 and Du 2 ) are defined as:…”
Section: Resultssupporting
confidence: 93%
“…5(a) -schematic illustration). In this case, the material having a higher EWF should have a larger adhesive force, since the atomic bond energy is proportional to ϕ 6 [17][18][19] and a larger atomic bond energy results in a higher surface energy (for surfaces having the same broken-bond density) [1,15,20]. The EWFs of both stainless steel samples are higher than that of Ti1, thus their larger frictional coefficients are expected.…”
Section: Resultsmentioning
confidence: 94%
“…where b ¼ 0:02233 GPa eV 6 is the average value for various crystal structures [9]. This relationship is illustrated in Figure 1 Thus, if the dependence of work function on temperature is established, the effect of temperature on the Young's modulus can be predicted.…”
mentioning
confidence: 98%